Parameter space for a dissipative Fermi-Ulam model - Oliveira, Diego F. M. (2011)
The parameter space for a dissipative bouncing ball model under the effect of inelastic collisions is studied. The system is described using a two-dimensional nonlinear area-contracting map. The introduction of dissipation destroys the mixed structure of phase space of the non-dissipative case, leading to the existence of a chaotic attractor and attracting fixed points, which may coexist for certain ranges of control parameters. We have computed the average velocity for the parameter space and made a connection with the parameter space based on the maximum Lyapunov exponent. For both cases, we found an infinite family of self-similar structures of shrimp shape, which correspond to the periodic attractors embedded in a large region that corresponds to the chaotic motion.